(untitled) (Bangladesh Journal of Psychiatry, 2020)
Homosexuality is defined as “the occurrence or existence of sexual attraction, interest and genitally intimate activity between an individual and other members of the same gender.” The objective of the study was to explore the behavior and experience of male homosexuals in Dhaka, Bangladesh. Due to hidden nature of this population, data were collected through a non-government organization working with them. This was a cross sectional study done during the period from March, 2009 to June, 2009. For this purpose, 102 male homosexuals were enrolled in the study by purposive sampling method and interviewed using a custom-built questionnaire. The results showed that all of the participants were biologically male with age ranged from 14-48 years and average age of first homosexual exposure for the participants was 11.75 years with a range from 4 to 27 years. The majority (56.9%) of the male homosexuals reported experiencing heterosexual intercourse. A high rate of sexual victimization history in childhood (64.7%) as well as in adulthood (49%) was reported. A sizable portion of the participants reported different discriminatory experiences including stigma and discrimination (48%), humiliation in public (49%), being cheated by male partner (60.8%), and exclusion from family (21.6%) because of their homosexual identity. Widespread childhood sexual abuse and discrimination clearly call for protective measures to be taken for safeguarding this vulnerable population. Bang J Psychiatry December 2016; 30(2): 41-44